Carbonate tufas as archives of climate and sedimentary dynamic in volcanic settings, examples from Gran Canaria (Spain). Issue 1 (20th July 2021) - Rodríguez‐Berriguete, Álvaro; Camuera, Jon; Alonso‐Zarza, Ana Maria
Abstract: Three Holocene tufas from Gran Canaria volcanic island were studied with the aim of deciphering their sedimentary evolution through space and time. Las Temisas tufa (south‐eastern arid part of the island) is dominantly composed of oncoids, intraclasts, phytoclasts, coated stems, minor thin stromatolites, and a high amount of siliciclastics. It was deposited in a fluvial system with variable flow velocities and palustrine conditions areas, which alternated with high energy events. Azuaje tufa (northern humid part of the island) is composed of coated stems, stromatolites, oncoids and phytoclasts, with relatively low amounts of siliciclastics, suggesting slow‐flowing and palustrine conditions and a relatively low incidence of (high energy) floodings. Los Berrazales tufa (north‐west of Gran Ganaria, the most humid one), is mainly composed of coated stems and crystalline crusts, formed in a laminar flow regime. Dominant clastic sedimentation in Las Temisas and high calcite growth rates in Los Berrazales led to a poor development of stromatolites in comparison with Azuaje. Las Temisas and Azuaje deposits have similar upward evolution with decreasing trend in siliciclastics and increasing trend in carbonates. However, Las Temisas has higher siliciclastic and lower phytoclastic contents suggesting a less vegetated area and more arid climate than in the other deposits. Additionally, tufas record local events common in volcanic terrains. Azuaje presents three units bounded by erosive discontinuities, which reveal significant erosion by enhanced runoff that could be caused by loss of vegetation due to wildfires related to volcanic eruptions at headwaters. Las Temisas record a possible interruption in sedimentation represented by aligned boulders due to rockfalls from the hillsides. These deposits formed from waters with similar chemistry providing to the carbonates their similar signals in δ 13 C–δ 18 O stable isotopes and 87 Sr/ 86 Sr ratios like that of the volcanic rocks. This work shows how, in volcanic areas, tufas are unique archives of the climate, vegetation and volcanic‐related processes, because all imprint the sedimentary regime of tufa deposition.